2018
DOI: 10.1159/000484688
|View full text |Cite
|
Sign up to set email alerts
|

Hypergastrinemia in Long-Term Use of Proton Pump Inhibitors

Abstract: Background/Aim: The use of proton pump inhibitors (PPIs) is known to lead to hypergastrinemia; however, the data in patients with atrophic gastritis is still lacking. The aim of this study was to investigate the effects of long-term PPIs use on the gastrin levels in patients with atrophic gastritis and to determine factors affecting hypergastrinemia in long-term users of PPIs. Methods: Serum Helicobacter pylori IgG, gastrin and pepsinogen levels were measured. Atrophic gastritis was assessed by upper gastroint… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 43 publications
2
17
0
Order By: Relevance
“…The statistical analysis showed that the higher rate of Ki67‐positive cells in the deeper layers of fundic glands and foveolar hyperplastic lesions in patients on PPIs was related to the larger size of FGPs, indicating that PPI treatment promotes proliferation of foveolar type epithelium in the deeper layer of FGPs. In addition to the obstruction of isthmus glands by parietal cell protrusion, a large amount of mucinous product from proliferating foveolar cells, which was promoted by PPI‐induced hypergastrinaemia due to decreased acid secretion and related factors, might enlarge fundic gland cysts and result in FGP enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…The statistical analysis showed that the higher rate of Ki67‐positive cells in the deeper layers of fundic glands and foveolar hyperplastic lesions in patients on PPIs was related to the larger size of FGPs, indicating that PPI treatment promotes proliferation of foveolar type epithelium in the deeper layer of FGPs. In addition to the obstruction of isthmus glands by parietal cell protrusion, a large amount of mucinous product from proliferating foveolar cells, which was promoted by PPI‐induced hypergastrinaemia due to decreased acid secretion and related factors, might enlarge fundic gland cysts and result in FGP enlargement.…”
Section: Discussionmentioning
confidence: 99%
“…Long-term human use of PPIs leads to hypergastrinemia in almost all cases, with fasting serum gastrin (FSG) levels increasing 3 to 5-fold in most subjects, but to much higher levels in 10% to 30% of cases [11]. Higher levels are seen in females and in those with atrophy of the gastric corpus due to CAG, whether auto-immune or due to Helicobacter pylori [27]. Recent studies, however, have shown that FSG levels in PPI users do not reflect the 4-or 5-fold elevations in mean serum gastrin concentrations that occur and persist after meals, particularly in females [28].…”
Section: Observations In Humansmentioning
confidence: 99%
“…This low incidence may be related to high rates of H. pylori infection in China. However, even in countries with high H. pylori infection rates, FGP frequency may be high, but these polyp have not been observed in several studies [40] . Frequency of FGPs is related to long-term PPI use.…”
Section: Discussionmentioning
confidence: 90%